2015
DOI: 10.4111/kju.2015.56.12.823
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of voiding dysfunction after transobturator tape procedure for stress urinary incontinence

Abstract: PurposeThe definition of posttransobturator tape procedure (post-TOT) voiding dysfunction (VD) is inconsistent in the literature. In this study, we retrospectively investigated the risk factors for post-TOT VD by applying various definitions in one cohort.Materials and MethodsThe medical records of 449 patients were evaluated postoperatively. Acute urinary retention requiring catheterization, subjective feeling of voiding difficulty during follow-up, and postoperative postvoid residual (PVR) greater than 100 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
3
0
3
Order By: Relevance
“…Observed risk factors can be preoperative voiding difficulties or exceeding the tension on the tape. Ahn et al in their study reported 10.5% patients had postoperative voiding difficulties, 2,2% needed prolonged catheterization due to retention and 0.4% underwent sling incision as a definite solution of voiding difficulties (22). Kim et al in their study reported an incidence of 9.5% of patients with transient retention (TR) and suggested that preoperative PVR can be noted as a risk factor for developing TR (23).…”
Section: Discussionmentioning
confidence: 98%
“…Observed risk factors can be preoperative voiding difficulties or exceeding the tension on the tape. Ahn et al in their study reported 10.5% patients had postoperative voiding difficulties, 2,2% needed prolonged catheterization due to retention and 0.4% underwent sling incision as a definite solution of voiding difficulties (22). Kim et al in their study reported an incidence of 9.5% of patients with transient retention (TR) and suggested that preoperative PVR can be noted as a risk factor for developing TR (23).…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, other studies have failed to demonstrate urodynamic predictors of post-MUS voiding dysfunction. Chang et al [ 34 ] postoperatively evaluated 449 patients who underwent TOT. Preoperative urodynamic parameters did not demonstrate reproducible predictors of voiding dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Er werd gestart met katheteriseren wanneer er sprake was van urineresiduen van 150 ml of meer na driemaal spontane mictie. De incidentie van mictieproblemen na een TOT loopt in de literatuur sterk uiteen en hangt af van de definitie die voor mictieproblemen wordt gehanteerd [9]. Hoe vaak de indicatie voor zelfkatheterisatie wordt gesteld, hangt ook af van hoe en op welk moment het urineresidu wordt vastgesteld en de afkapwaarde die voor het post void residual (PVR) wordt gehanteerd.…”
Section: Discussieunclassified
“…Hoe vaak de indicatie voor zelfkatheterisatie wordt gesteld, hangt ook af van hoe en op welk moment het urineresidu wordt vastgesteld en de afkapwaarde die voor het post void residual (PVR) wordt gehanteerd. De incidentie van de noodzaak tot katheterisatie na een TOT loopt in de verschillende studies dan ook uiteen van 2,2 tot 22 % [9][10][11][12].…”
Section: Discussieunclassified
See 1 more Smart Citation